Critical analysis of ideas on the learning readiness of children - Quibuyen, Liezl Neri (2005)
This study is an investigation of the common indicators of learning readiness of the five selected thinkers as applied and evident in the classroom of one of the private elementary school. Three questions gave rise to this study: (1) What learning ideas are found to be common among the selected thinkers? (2) What are the common indicators of learning readiness as assumed or discussed in the works of the selected thinkers? (3) What principles of learning readiness are usually followed or applied in the classroom in one of the private elementary school? The following results were derived from the data generated: the principles of learning readiness exemplified by the selected thinkers in the past centuries are present and evident through the observable skills of Grade One entrants. There exists commonality in some of the learning ideas of the selected thinkers and there is commonality in the indicators of learning readiness such as their concept of creative ability, interest in school instruction, interest in physical activity (gross motor skills), self-activity, sensory perception and social interaction. Analysis of data suggests the following recommendations: teachers need to foster an environment which strengthens the creative capacities and interest of the children. Furthermore, an early childhood program should be planned around the skills level of the children in class.
"March, 2005."
Thesis (M.A. Education : Philosophy of Education)--University of the Philippines Diliman.
Keywords: Critical thinking in children -- Philippines; Readiness for children -- Philippines; Cognitive learning -- Philippines